The Land of Saddle-bags : A Study of the Mountain People of Appalachia - Raine, James Watt, 1869-1949 (Book collections on Project MUSE., 1997)
This charming account of life in Appalachia at the turn of the century is one of the three most important books from the early twentieth century that, as Dwight Billings writes in his foreword, have ""had a profound and lasting impact on how we think about Appalachia and, indeed, on the fact that we commonly believe that such a place and people can be readily identified."" Originally published in 1924, it was advertised as a ""racy book, full of the thrill of mountain adventure and the delicious humor of vigorously human people."" James Watt Raine, professor of English literature and later hea.